Successful Treatment of Ocular Chronic Lymphocytic Leukemia with Ibrutinib: Case Report and Review of the Literature. (2020) - Chauhan, Ayushi F; Viruni, Narine; Alvin Liu, T.Y.; Arevalo, J Fernando; Cheson, Bruce D
Abstract: Clinically apparent neurological involvement by chronic lymphocytic leukemia (CLL), especially ocular manifestations, is rare. Standard diagnostic approaches for neurological or ocular CLL, including neuroimaging, have low yield and sensitivity and CSF flow cytometry remains the gold standard. Optical coherence tomography can yield helpful data and usually shows retinal pigment epithelial disruptions which may persist despite clinical improvement and resolution of MRI abnormalities. Our patient with ocular relapse with leukemic retinopathy and choroidal involvement was successfully treated with Ibrutinib monotherapy, lasting more than 2 years, highlighting the safety and efficacy of this agent regardless of site or type of relapse.